Effects of Nifedipine on Cation Transport and Na - K-ATPase Activity in Erythrocytes and Electrolyte Homeostasis in Rats - Shaheen, Najma; Mahboob, Tabassum (Journal of Basic & Applied Sciences, 2012)
Calcium channel antagonists have been reported to reduce blood pressure in those individuals at risk of cardiac and cerebrovascular events. There is no specific study available regarding the role of electrolyte alterations in blood pressure lowering effects of nifedipine. The present study was designed to investigate the role of electrolyte homeostasis, changes in ouabain-sensitive Na+ K+ adenosine triphosphatase (ATPase) activity, and net sodium efflux and potassium influx across blood cell membranes. Rats were divided into two experimental groups . Nifedipine (20mg/ kg body weight ) was administered by gastric tube to the test group . Control group received same volume of deionize water .The intra-erythrocyte sodium, serum sodium, potassium, calcium and sodium, calcium content of heart and kidney tissues were decreased significantly. Whereas, intra-erythrocyte potassium was slightly decreased or remained normal in nifedipine treated rats as compared to normal healthy rats. The Na - K - ATPase activity, serum magnesium, potassium and magnesium content in heart and kidney tissues were increased significantly. Results confirmed that nifedipine represses ion channels, transporters and calcium-binding proteins in tissues. Erythrocyte studies indicate that nifedipine blocks the entrance of calcium into the cells but also stimulate Na - K - ATPase activity, resulting in reduction of intracellular sodium concentration, thus suggesting direct nifedipine-induced blood pressure reduction.